An Efficient Synthetic Method and Theoretical Calculations of Olmesartan Methyl Ether: Study of Biological Function of AT1 Antagonism - Ntountaniotis, Dimitrios; Agelis, George; Resvani, Amalia; Halabalaki, Maria; Liapakis, George; Spyridaki, Katerina; Golic Grdadolnik, Simona; Merzel, Franci; Kostidis, Sarantos; Potamitis, Constantinos; Tselios, Theodore; Matsoukas, John; et al. (Combinatorial Chemistry & High Throughput Screening, 2014)
The dissolution of the antihypertensive AT1 antagonist olmesartan in methanol generates in situ a new highly bioactive methyl ether analogue via SN1 mechanism involving an intramolecular proton transfer from carboxyl to hydroxyl group. Theoretical calculations confirmed the thermodynamic control preference of methyl ether versus the antagonistic product methyl ester. Α facile synthetic method for olmesartan methyl ether from olmesartan or olmesartan medoxomil is also described. Interestingly, the introduction of the methyl group to olmesartan did not alter its pharmacological properties. This observation opens new avenues in the synthesis of novel drugs, since hydroxyl and carboxylate groups have an orthogonal relationship in many drugs.
Keywords: olmesartan